After Juliet - MacDonald, Sharman 1951- (Faber and Faber, 2001)
"A tense truce holds between the Capulets and the Montagues after the deaths of Romeo and Juliet. Benvolio, Romeo's best friend, is in love with Rosaline, Juliet's cousin; but Rosaline is bent on revenge. After Juliet by Sharman Macdonald was specially commissioned by the Royal National Theatre for the BT National Connections Scheme for young people." Klappentext
Keywords: Jugend; Children's plays, English; Conflict of generations -- Juvenile drama; Revenge -- Juvenile drama; Youth -- Juvenile drama; Verona (Italy) -- Juvenile drama; Theaterstück